Kiwisaldula (Hemiptera: Heteroptera: Saldidae) from the South Island of New Zealand: new species and identification key - Larivière, Marie-Claude; Larochelle, André (Zootaxa, 2018)
Kiwisaldula cranshawi new species, K. januszkiewiczi new species, K. ryani new species, and K. yangae new species are described from the South Island of New Zealand. Morphological descriptions are provided together with illustrations emphasising the most important diagnostic features of external morphology and male genitalia. Information is given on synonymy, type specimens, material examined, geographic distribution and biology.